An index to evaluate the fluvial habitat degradation in lowland urbanstreams - Cochero, Joaquin (2016)
The objective of the present article is to propose an index that allows the assessment of the fluvial habitat quality in lowland streams that run through urbanized areas, by the use of metrics related to the quality of the watercourse, the river banks, the riparian zone and the fluvial geomorphology. The metrics retained in the index (USHI, Urban Stream Habitat Index) include the cover percentage and quality of the aquatic vegetation; the main features of the river banks; the presence of exotic trees, of litter, of permanent structures (such as buildings) in the riparian zone and other major geomorphological alterations, such as dredging or channelization. The index is related to physical-chemical parameters that are linked to water quality, the imperviousness of the watershed and to other biotic descriptors, particularly the macroinvertebrate and diatom assemblages. The values of the index for the sites in the studied area revealed that 41.2% have a bad or very bad habitat quality, 27.8% a moderate habitat quality, while 31% have a good or very good habitat quality. The main issue detected in the studied sites involved the dredging or partial channelization of the reaches. Unlike other indices that evaluate the quality of the physical habitat through the use of the diatoms or macroinvertebrate communities, the USHI can be interpreted as a measure of the overall quality of the habitat, and uses indicators that do not require the identification of taxa, making it more accessible to non-specialists. Therefore it provides with a tool to evaluate the fluvial habitat quality of lowland streams that can be easily applied, particularly by professionals that take part in the management and decision making process regarding urbanized watersheds.